2008
DOI: 10.1021/nn800244k
|View full text |Cite
|
Sign up to set email alerts
|

Nanometal-Decorated Exfoliated Graphite Nanoplatelet Based Glucose Biosensors with High Sensitivity and Fast Response

Abstract: We report the novel fabrication of a highly sensitive, selective, fast responding, and affordable amperometric glucose biosensor using exfoliated graphite nanoplatelets (xGnPs) decorated with Pt and Pd nanoparticles. Nafion was used to solublize metal-decorated graphite nanoplatelets, and a simple cast method with high content organic solvent (85 wt %) was used to prepare the biosensors. The addition of precious metal nanoparticles such as platinum (Pt) and palladium (Pd) to xGnP increased the electroactive ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
222
1
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 417 publications
(229 citation statements)
references
References 35 publications
(82 reference statements)
3
222
1
3
Order By: Relevance
“…However, the poor electronic conductivity of metal oxides (for example, Co 3 O 4 in B10 À 5 S m À 1 at room temperature) significantly impedes them from wide use in electrochemical biosensing devices with high sensitivity and reliability, fast response and excellent selectivity 10,14,15 . One of major strategies to enhance charge transport in electrochemical biosensors is to design composite materials by combining highly electrocatalytic materials with a conductive substance [16][17][18][19][20] , whereas single-and multi-walled carbon nanotubes (CNTs) [21][22][23][24][25] , graphene 26,27 and noble metal nanoparticles 28 have been explored to serve as conductive pathways of metal oxides (TiO 2 , MnO 2 , RuO 2 , Co 3 O 4 and NiO). Although these low-dimensional composite nanostructures could provide extremely large specific surface area of the electrode/electrolyte interface [16][17][18][19][20][21][22][23][24][25][26][27][28] , the assembled electrodes exhibit an undesirably low electronic conductance as a consequence of exceptionally low electron transport in the nanomaterials as well as the high contact resistances within nanomaterials and between the current collector and electrodes 29,30 , greatly hindering their potential applications in electrochemical biosensors at ultralow concentrations in unconventional body fluids.…”
mentioning
confidence: 99%
“…However, the poor electronic conductivity of metal oxides (for example, Co 3 O 4 in B10 À 5 S m À 1 at room temperature) significantly impedes them from wide use in electrochemical biosensing devices with high sensitivity and reliability, fast response and excellent selectivity 10,14,15 . One of major strategies to enhance charge transport in electrochemical biosensors is to design composite materials by combining highly electrocatalytic materials with a conductive substance [16][17][18][19][20] , whereas single-and multi-walled carbon nanotubes (CNTs) [21][22][23][24][25] , graphene 26,27 and noble metal nanoparticles 28 have been explored to serve as conductive pathways of metal oxides (TiO 2 , MnO 2 , RuO 2 , Co 3 O 4 and NiO). Although these low-dimensional composite nanostructures could provide extremely large specific surface area of the electrode/electrolyte interface [16][17][18][19][20][21][22][23][24][25][26][27][28] , the assembled electrodes exhibit an undesirably low electronic conductance as a consequence of exceptionally low electron transport in the nanomaterials as well as the high contact resistances within nanomaterials and between the current collector and electrodes 29,30 , greatly hindering their potential applications in electrochemical biosensors at ultralow concentrations in unconventional body fluids.…”
mentioning
confidence: 99%
“…In case of glucose biosensors fabricated with a GR-based composite, Chitosan-flat GR/Au nanocomposite films were also reported as a potential glucose biosensor due to their good amperometric response to glucose with wide linear ranges 81) . The glucose biosensor fabricated with Pt-graphite nanoplatelets was suggested as an enhanced glucose biosensor as well and showed a high sensitivity and selectivity 82) . The results revealed that the graphite nanoplatelets incorporated into the biosensor interface increased the effective electrode surface area.…”
Section: Glucose Biosensorsmentioning
confidence: 99%
“…Functionalization of this CVD-grown 2D graphene is one of the important aspects to manipulate the intrinsic graphene properties (high conductivity and electron mobility) for its booming applications. The graphene sheet can be readily functionalized via covalent C-C coupling [19,20] or non-covalent p-p interaction [21,22]. Modifying the graphene surface with desired functional groups by chemical treatment (covalent functionalization) is one of the convenient strategies to get well-dispersed functional groups on the graphene basal plane.…”
Section: Introductionmentioning
confidence: 99%
“…Modifying the graphene surface with desired functional groups by chemical treatment (covalent functionalization) is one of the convenient strategies to get well-dispersed functional groups on the graphene basal plane. However, such approaches lead to the presence of non-conducting agents on the graphene surface and the uncontrolled creation of defect sites that would undermine the electronic properties and alter the band structure of the pristine graphene [19,20]. Conversely, a non-covalent functionalization approach [21,22] involving van der Waals forces or p-p stacking of functionalizing moiety on the graphene sheet could provide selective functional groups on graphene surface's nearly perfect crystal structure retaining its intrinsic electronic properties and sensitivity.…”
Section: Introductionmentioning
confidence: 99%